Peningkatan Keterampilan Komunikasi Melalui Pembelajaran Window Shopping Berbasis Diferensiasi Konten dan Proses pada Materi Jaringan - Febriyanto; Sumarno; Dies Hendra WW (Pascasarjana Universitas PGRI Semarang, 2024)
This research aims to improve students' communication skills through the application of the window shopping learning model for tissue lessons in class XI-6 SMA Negeri 9 Semarang. This type of research is Collaborative Classroom Action Research (PTKK) and is carried out in 2 research cycles. The research subjects were 36 students in class XI-6 of SMA Negeri 9 Semarang. The objects of research are oral, written and interpersonal communication skills. The instruments used are observation and documentation sheets. The results of the research conducted showed that there was an increase in students' oral, written and interpersonal communication skills which were observed from the pre-cycle, cycle I and cycle II. Oral communication skills in pre-cycle were 44.4% in the sufficient category, cycle I was 58.3% in the sufficient category and in cycle II were 75.9% in the good category, while written communication skills in the pre-cycle were 57.4% in the sufficient category, cycle I 72.3% in the good category and in the second cycle 82.2% in the very good category, as well as interpersonal communication skills in the pre-cycle 61.1% in the good category, in the first cycle 71.0% in the good category and in the second cycle it was 82.26 very good category.